G502(P) Risk assessment of children with eating disorders: a retrospective analysis of inpatient admissions. (27th April 2015) - Swinburne, C
Abstract : Background: In 2012 the Royal College of Psychiatrists published the Junior MARSIPAN guideline on the management of anorexia nervosa in patients under 18 years of age. A risk assessment framework was proposed at this time to aid identification of patients at risk of serious complications. Aim: To evaluate current clinical practice, with a focus on risk assessment at time of admission, and to compare this with the risk assessment framework proposed by the Royal College of Psychiatrists. Methods: All patients with an eating disorder requiring paediatric inpatient admission were identified over the period of June 2009 to February 2014. A retrospective casenote analysis was performed and data extracted using a standard proforma. Initial assessment of each patient was reviewed for documentation of BMI, weight, cardiovascular health (heart rate, syncope, significant orthostatic changes, irregular heart rate), ECG abnormalities, hydration status, temperature, biochemical abnormalities, disordered eating behaviours, engagement with management plan, activity and exercise, muscular weakness, self-harm/suicide, other mental health diagnoses as well as other potential co-existing risk factors. Results: A total of 14 patients were identified with 22 admissions over the data collection period. 15 patients were admitted electively via the local CAMHS team, 4 patients via A&E and 3 patients following GP referral. No patients had a formal risk assessment performed. Assessment performed at the time of admission was highly variable. With the information available 10 patients were categorised as high risk, 11 patients were categorised as alert to high concern, and 1 admission was categorised as moderate risk. No patients were classified as low risk. Conclusion: This study highlighted the fact that children with eating disorders are treated in paediatric inpatient wards as well as in specialist centres. Admissions to the paediatric wards are infrequent. Initial assessment and investigation of this patient group is highly variable and does not adhere to current guidance. Implementation of a formal risk assessment framework is required in order to identify patients at risk of complications. The development of specific admission documentation based on Royal College guidance would aid assessment and help guide inpatient management, thereby providing a more consistent approach to patient care.